Determinan keputusan berkunjung pada desa berbasis budaya: Peran faktor sosial, budaya, dan motivasi berwisata - Arisanti, Any; Suswati, Endang; Muda Priyatna, Navi (Nur Science Institute, 2026)
This study aims to analyze the influence of social and cultural factors on tourists’ visiting decisions to Kampung Majapahit Tourism Village in Trowulan District, Mojokerto Regency, with travel motivation as a mediating variable. The research object consisted of 156 tourist respondents selected proportionally. A quantitative, descriptive-explanatory approach was applied, using Likert-scale questionnaires, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS software. The findings reveal that both social and cultural factors have direct and significant effects on visiting decisions and exert indirect effects through travel motivation, which serves as a significant mediator. Travel motivation plays a crucial role in linking external social and cultural influences to tourists’ behavioral decisions. The study concludes that strengthening social interactions, preserving cultural values, and developing motivation-based tourism strategies are essential to enhancing sustainable cultural tourism visits.